2021
DOI: 10.1503/cmaj.210659
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of childhood cancer in Canada during the COVID-19 pandemic

Abstract: oncerns have been raised that the COVID-19 pandemic disrupted health care-seeking behaviours and access to health care, affecting the diagnosis and management of other conditions such as cancer. Studies conducted in the Netherlands and United Kingdom using administrative data have shown as much as a 50% reduction in cancer incidence in adults after March 2020. 1,2 Other studies in adult populations thus far have shown a decrease in the number of new cancer diagnoses, and cancer-related medical visits, therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(54 reference statements)
0
7
1
Order By: Relevance
“…Worldwide, substantial disruptions in pediatric cancer diagnosis and management were described in the first pandemic wave, particularly in low- and middle-income countries. 74 Whereas a study conducted in the UK reported a significant reduction in cancer diagnoses during the first wave, 75 however, two studies from Canada and Germany 76 , 77 did not find a decrease in the first pandemic year. These heterogeneous published data, combined with the insufficient statistical power of our pediatric series which did not allow us to analyze incident cases according to pandemic waves for all tumor types, mean that our estimates must be interpreted with great caution.…”
Section: Discussionmentioning
confidence: 97%
“…Worldwide, substantial disruptions in pediatric cancer diagnosis and management were described in the first pandemic wave, particularly in low- and middle-income countries. 74 Whereas a study conducted in the UK reported a significant reduction in cancer diagnoses during the first wave, 75 however, two studies from Canada and Germany 76 , 77 did not find a decrease in the first pandemic year. These heterogeneous published data, combined with the insufficient statistical power of our pediatric series which did not allow us to analyze incident cases according to pandemic waves for all tumor types, mean that our estimates must be interpreted with great caution.…”
Section: Discussionmentioning
confidence: 97%
“… 18 Nevertheless, when the pre-pandemic years (2017-2020) and the 6 months of the pandemic period were compared in a study performed in Canada, no statistically significant difference was observed in childhood cancers. 21 The same study also reported no increase in metastatic disease and early mortality during the pandemic period. The present study determined that the number of newly diagnosed patients during the pandemic increased by 2 times compared to the pre-pandemic period, but similar to other studies, the application times were prolonged.…”
Section: Discussionmentioning
confidence: 83%
“…Although a decrease in the number of newly diagnosed patients and delays in admission was reported in previous studies, 18 - 20 there was no statistical difference in a comprehensive study performed in Canada. 21 It is known that these delays in cancer diagnosis are more common in adults during the pandemic period. According to the results of our study, although the admission time of newly diagnosed patients was 15 days later during the pandemic period, it was observed that this delay period did not increase the rate of advanced disease.…”
Section: Discussionmentioning
confidence: 99%
“…2,7 There are few reports of pediatric centers with stable or increased rates of new oncologic diagnoses during the COVID-19 pandemic. 8,9 A retrospective chart review was conducted of patients diagnosed with nonrelapsed leukemia or lymphoma at Cohen Children's Medical Center (CCMC) from March 2018 until May 2021. CCMC is one of the tertiary care pediatric hospitals in the area with a catchment that includes New York City and the surrounding suburbs.…”
Section: E T T E R T O T H E E D I T O R New Pediatric Leukemia/lymph...mentioning
confidence: 99%
“…2 , 7 There are few reports of pediatric centers with stable or increased rates of new oncologic diagnoses during the COVID‐19 pandemic. 8 , 9 …”
mentioning
confidence: 99%